PATTERN OF SEXUALLY TRANSMITTED DISEASES IN PATIENTS PRESENTING AT AYUB TEACHING HOSPITAL, ABBOTTABAD - Razvi, Syed Kamran Amir; Najeeb, Shahzad; Nazar, Hassan Shahzad (Journal of Ayub Medical College Abbottabad, 2014)
Background Sexually transmitted diseases are present in all societies across the globe. Different cultures and societies show a different spectrum of these diseases. The last study conducted in Hazara division was back in 1995. We have conducted this study to see the recent trends and patterns of sexually transmitted diseases in the region. Methods: This cross-sectional study was conducted in Ayub Teaching Hospital, Abbottabad and included patients over a five year period from January 2010 till December 2014. Case sheets of 512 presenting with sexually transmitted diseases whose diagnosis was confirmed by related lab investigation were analysed retrospectively. Patients of all ages and both sexes were included. Results Out of these 512 patients only 47 were females and 465 were males. The age varied from 15-66 years. Gonorrhoea was the commonest disease with 231 cases. Genital warts were diagnosed in 60 cases. Non-gonococcal urethritis was seen in 57 patients. Genital Molluscum contagiosum was seen in 45 patients. Syphillis was diagnosed in 41 patients. Thirty-one cases of herpes genitalis, 25 cases of Chancroid, 13 cases of Lymphogranuloma venereum, were also seen. Five patients were found positive for HIV. Overwhelming majority of the patients were between the age of 19-35 years. 61% of the patients were married. The source of infection in male patients was mainly prostitutes (70%) but also included homosexual boys (21 %), married women (7.5%) and eunuchs (1.5%). The main source of infection in females was from husbands. Conclusion The number ofSTD patients presenting in the region has increased significantly. The main factor is obviously the rise in population but also signifies the change in cultural and moral values. Keywords: Sexually transmitted diseases, recent trends, social values